MITIGASI RESIKO KREDIT PERBANKAN - Fitriani Jamaluddin (Hukum Ekonomi Syariah, Fakultas Syariah, IAIN Palopo, 2018)
There are two purpose of this research : (1) To explain the law risk that can arise in giving loan by Banking. (2) To explain the form of risk mitigation by Banking. This research is normative research. And the type of this research is library research. The result of this research, noticing banking sector is a high risk sector, it means that susceptible to risk, one of the risks that really hard to handle is loan risk. Banking should do some deep analysis before giving the loan, by using 4P, 5C, and 3R Principle